Alpha-Synuclein Aggregates Associated with Mitochondria in Tunnelling Nanotubes - Valdinocci, Dario; Kovarova, Jaromira; Neuzil, Jiri; Pountney, Dean L (Neurotoxicity research, 2021)
The interaction of α-synuclein with mitochondria in both typical and atypical Parkinson's disease is a critical component of degeneration. The mechanism of cell-to-cell propagation of pathological α-synuclein in synucleinopathies is unclear. Intercellular exchange of mitochondria along tunnelling nanotubes has been described in other diseases, such as cancer; however, its role in synucleinopathies is unknown. Pathological α-synuclein species have been demonstrated previously to move from cell to cell via tunnelling nanotubes. This process was further explored using co-culture and monoculture systems to determine if α-synuclein binds to migrating mitochondria within tunnelling nanotubes. Super-resolution analysis via stimulated emission depletion microscopy showed interaction between α-synuclein with the mitochondrial outer membrane and the presence of alpha-synuclein associated with mitochondria in tunnelling nanotubes between 1321N1, differentiated THP-1 and SH-SY5Y cell types. siRNA knockdown of Miro1, a critical protein-bridging mitochondria to the motor adaptor complex, had no effect on mitochondrial density or α-synuclein association with mitochondria in tunnelling nanotubes. The results show that α-synuclein aggregates associate with mitochondria in intercellular tunnelling nanotubes, suggesting that mitochondria-mediated α-synuclein transfer between cells may contribute to cell-to-cell spread of α-synuclein aggregates and disease propagation.
Keywords: kokultivační techniky; alfa-synuklein; Coculture Techniques; nádorové buněčné linie; nanotrubičky; Mitochondria; patologická konformace proteinů; Protein Aggregation, Pathological; Miro1; Parkinson’s disease; Tunnelling nanotube; Humans; mitochondrie; Cell Line, Tumor; Alpha-synuclein; Nanotubes; alpha-Synuclein; lidé